ESG as a Global Norm: Unilever’s Role in Promoting Sustainability Through International Governance - Andi Septiani; Akim Akim; Irman Gurmilang Lanti (Green Publisher Indonesia, 2026)
This study aims to analyze Unilever's implementation of Environmental, Social, and Governance (ESG) principles as part of the company's sustainability strategy and its contribution to sustainable global governance. ESG has evolved into a global framework implemented by multinational companies, including Unilever, that are committed to reducing environmental impact, improving social well-being, and adhering to the principles of good governance. This research uses a qualitative method with a case study approach and an institutional analysis perspective. Data were obtained through literature review and interviews with relevant parties, including companies, governments, and local communities. The results show that Unilever has successfully adapted global ESG norms into local policies in Indonesia through the Unilever Sustainable Living Plan (USLP) and Unilever Compass programs. However, despite progress in reducing carbon footprint and improving social well-being, challenges still exist in implementing ESG in areas beyond the direct control of companies, especially when it comes to plastics and recycling. The conclusion of this study is that multinational companies, such as Unilever, play an important role in influencing global sustainability policies by collaborating with a wide range of stakeholders, but local challenges still require special attention in achieving global sustainability goals.